Modification of Marine Natural Product Ningalin B and SAR Study Lead to Potent P-Glycoprotein Inhibitors - Chao Yang; Iris L. K. Wong; Wen Bin Jin; Tao Jiang; Larry M. C. Chow; Sheng Biao Wan (Marine Drugs, 2014)
In this study, new marine ningalin B analogues containing a piperazine or a benzoloxy group at ring C have been synthesized and evaluated on their P-gp modulating activity in human breast cancer and leukemia cell lines. Their structure-activity relationship was preliminarily studied. Compounds 19 and 20 are potent P-gp inhibitors. These two synthetic analogues of permethyl ningalin B may be potentially used as effective modulators of P-gp-mediated drug resistance in cancer cells.